Evidence for transfer of cellular and humoral immunity to cytomegalovirus from donor to recipient in allogeneic bone marrow transplantation. - Boland, G J (1992)
In order to study the importance of the immune status of the donor in the development of immunity after allogeneic bone marrow transplantation (BMT), we monitored 23 cytomegalovirus (CMV) antibody-positive BMT recipients for humoral and cellular immunity to CMV, of whom 12 had a CMV antibody-positive and 11 a CMV antibody-negative marrow donor. Lymphocyte proliferation to CMV recovered significantly earlier after BMT in recipients of marrow from a CMV+ donor (10.4 weeks after BMT) compared with the recipients of marrow from CMV- donors (16.7 weeks after BMT, P less than 0.05). This seemed to be specific, as lymphocyte proliferation to phytohaemagglutinin and Candida were not different between the to groups. IgM responses after active infection were seen in both groups, but initial IgG rises without IgM were seen only in recipients of marrow from CMV+ donors (P less than 0.05). Lymphocyte proliferative or humoral immune responses to CMV were not detected in any of the patients in a control group consisting of nine CMV- recipients. These results indicate that T cell memory to CMV is transferred with donor marrow from CMV+ donors, leading in most patients to direct IgG anti-CMV responses and to quicker recovery of cellular immunity to CMV.